Mapping the ASEAN YouTube Uploaders - Albertus Magnus Prestianta (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
YouTube can now be categorized as mainstream media. It can be seen as a disruptive force in business and society, particularly concerning young people. There have been several recent studies about YouTube, providing essential insights on YouTube videos, viewers, social behavior, video traffic, and recommendation systems. However, research about YouTube uploaders has not been done much, especially YouTube uploaders from ASEAN countries. Using a combination of web content mining and content analysis, this paper reviews 600 YouTube uploaders using the data of Top 100 favorite YouTube uploaders in six ASEAN countries (Indonesia, Singapore, Malaysia, Thailand, Vietnam, and the Philippines), which are retrieved from NoxInfluencer. The study aims to provide a wider picture of YouTube uploaders' characteristics from six ASEAN countries. This study also provides useful information about how to retrieve web documents using Google Web Scrapper automatically. The study results found that the entertainment category dominated the top 100 positions of the NoxInfluencer version. In almost every country analyzed, channels related to news and politics are less attractive to YouTube users. For YouTube uploaders, YouTube can be a potential revenue source through advertising or in collaboration with specific brands. Through the analysis, we discovered that engagement is the critical factor in generating income in the form of likes, dislikes, and comments.